“The People Who Stayed”: Back River Memorial Gardens Cemetery as a Site of Jewish Migrant and Montreal Urban Meaning-Making - Frost, Naomi; Sheftel, Anna (Urban History Review / Revue d'histoire urbaine, 2024)
Keywords: Ahuntsic; Cimetières; Juifs

« Glad of your help »: Scottish Architects in Montreal, 1860-1940 - Adams, Annmarie (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Golden Square Mile; Royal Victoria Hospital; Écossais

Du «pacte entre les deux peuples fondateurs» à la «société distincte». L'instrumentalisation de la Révolution tranquille dans les débats linguistiques et constitutionnels au Québec, 1967-1982 - Brousseau Desaulniers, Antoine (La Révolution tranquille entre l’ici et l’ailleurs, 2024)
Keywords: Anglophones; Francophones; Langue

« Dear Richard...send us a few buffalo tongue »: Donald Smith's Fur Trade Contacts and Peronal Credit Networks - Hamon, Max (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Autochtones; Bourgeoisie; Chemins de fer; Femmes; Fourrure; Golden Square Mile

One long line of marvel: 200 years of Montreal's St. Patrick's parade - Hustak, Alan (Véhicule press, 2024)
Keywords: Irlandais; Processions

Jackie Robinson...Un Américain à Villeray - Tessier, Stéphane (Il était une fois...Montréal-Nord, 2024)
issued: 2024-23-00
Keywords: Baseball; Noirs; Villeray

La paroisse Holy Family: une empreinte de la présence anglophone dans l'arrondissement - Vailles, Alexis (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2024)
Keywords: Anglophones; Rosemont; Églises

Du Centro Donne Italiane di Montréal aux Donne d’Acciaio. - Lebleu, Jacques (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2023)
Keywords: Ahuntsic; Femmes; Féminisme; Italiens

Tim Tim? Bwa Chèch! : Documentation de la présence des artistes visuels haïtiens à Montréal 1971-1986 - Theliar-Charles, Kessie (Université Concordia, 2023)
Keywords: Haïtiens

“The Most Distinctively Canadian City” Representations of the City in Montreal Guidebooks, 1876–1892 - Lamoureux, François (Urban History Review/Revue d'histoire urbaine, 2023)
Keywords: Anglophones; Métropole; Tourisme

Il fallait se défendre: l'histoire du premier gang de rue haïtien à Montréal - Aurélien, Maxime; Rutland, Ted (Mémoire d'encrier, 2023)
Keywords: Criminalité; Délinquance; Haïtiens; Noirs

The harp and the shamrock: the two faces of Montreal's Irish community - Bâby, Françoise (The Westmount Historian, 2023)
Keywords: Griffintown; Irlandais

« Le Québec connaîtrait-il l’agonie du Chili ? » : l’influence de « l’expérience chilienne » sur l’évolution du Parti québécois au tournant des années 1970 - Barry-Shaw, Nikolas (Bulletin d'histoire politique, 2023)
Keywords: Chiliens; Indépendantisme; Partis politiques

Where They Stood: The Evolution of the Black Anglo Community in Montreal (Linda Leith Publlishing, 2023)
Keywords: Anglophones; Noirs

Le Canada français à l’épreuve du pluralisme culturel et religieux : les Juifs dans le discours de L’Action nationale (1933-1948) - Croteau, Jean-Philippe (Mens, 2023)
issued: 2023-23-00
Keywords: Action nationale (L'); Juifs; Nationalisme

Du pragmatisme à l’engagement. Les militants chiliens à Montréal et leurs relations avec le milieu politique local : influences et interactions réciproques - Del Pozo, José (Bulletin d'histoire politique, 2023)
Keywords: Chiliens

À la défense du peuple chilien : la connexion religieuse québécoise avec la résistance chilienne durant la dictature d’Augusto Pinochet - Demers, Maurice (Bulletin d'histoire politique, 2023)
Keywords: Chiliens; Missions

Du Chili d’Allende au Québec : inspirations et parcours du Réseau des politisés chrétiens (1969‑1972) - Foisy, Catherine; Genois-Lefrançois, Christophe (Bulletin d'histoire politique, 2023)
Keywords: Chiliens

Les Québécois et la solidarité avec le Chili, 1970‑1990 - Hervas, Roberto (Bulletin d'histoire politique, 2023)
Keywords: Chiliens; Confédération des syndicats nationaux

S'unir dans l'émotion: le Congrès international de 1929, moment charnière d'affirmation des gardes-malades canadiennes-françaises - Klein, Alexandre; Larose-Dutil, Hubert (Revue d'histoire de l'Amérique française, 2023)
Keywords: Femmes; Francophones; Infirmières

« The inalienable right to existence »: Corinne Rocheleau-Rouleau, militante pour l'instruction des personnes sourdes et historienne des francophones d'Amérique - Lavoie, Pierre (Profession historienne? Femmes et pratique de l’histoire au Canada français, XIXe-XXe siècles, 2023)
Keywords: Femmes; Francophones; Histoire; Sourds

Le High School of Montreal: fer de lance de l'enseignement anglo-protestant - MacLeod, Roderick; Poutanen, Mary Anne (Atlas historique du Québec. L'école au Québec, 2023)
Keywords: Anglophones; High School of Montreal; Protestants

Scolariser les enfants juifs - MacLeod, Roderick; Poutanen, Mary Anne; Dufour, Andrée (Atlas historique du Québec. L'école au Québec, 2023)
Keywords: Juifs

Statesman of the Piano: Jazz, Race, and History in the life of Lou Hooper - Mills, Sean; Fillion, Eric; Rochat, Désirée (McGill-Queen's University Press, 2023)
Keywords: Musique

John George Savage. Un habitant notable de Dorval/John George Savage. A notable Dorval resident - Nieuwendyk, Dick (Héritage Dorval, 2023)
Keywords: Anglicans; Dorval; Peinture

BRAININ, REUBEN - Orenstein, Eugene (Dictionnaire biographique du Canada, 2023)

« Des mots et des commandements déplacés ». La prise en charge des étudiants vietnamiens du Plan Colombo à l’Université de Montréal (1950–1959) - Poitras, Daniel (Historical Studies in Education / Revue d'histoire de l'éducation, 2023)
issued: 2023-23-00
Keywords: Université de Montréal; Vietnamiens; Étudiants

Le boulevard Saint-Laurent et son histoire-(suite 1) - Tessier, Stéphane (Il était un fois... Montréal Nord, 2023)
issued: 2023-21-00
Keywords: Juifs; Saint-Laurent (rue)

Le boulevard Saint-Laurent et son histoire-(suite 2) - Tessier, Stéphane (Il était un fois... Montréal Nord, 2023)
issued: 2023-22-00
Keywords: Chinois; Juifs; Saint-Laurent (rue)

Dos blaybt tsu zen : le journal yiddish de Montréal, Der Keneder Odler, Maurice Duplessis et le Québec, 1936-37. - Victor, Sacha (Université d'Ottawa, 2023)
Keywords: Juifs

“A Curse or a Blessing?”: Montreal Jews and the Politics of 1960s Quebec - Lacasse, Simon-Pierre (Canadian Historical Review, 2022)
Keywords: Juifs; Nationalisme

Parcours migratoires et re-constructions identitaires de femmes d'ascendance maghrébine à Montréal - Boukerrou, Yasmine (Université du Québec à Montréal, 2022)
Keywords: Femmes; Maghrébins

Red mitten nationalism: sport, commercialism, and settler colonialism in Canada - Fresco, Estée (McGill-Queen's University Press, 2022)
Keywords: Autochtones; Jeux olympiques; Nationalisme

La Petite-Bourgone: bercail de l'industrie et quartier historique multiracial de Montréal - High, Steven (Bulletin de l'AQPI, 2022)
issued: 2022-22-00
Keywords: Anglophones; Canadien National; Francophones; Grand Tronc; Lachine (canal); Montreal Rolling Mills; Noirs; Petite-Bourgogne; Quartiers; Sainte-Cunégonde

Deindustrializing Montreal: Entangled Histories of Race, Residence, and Class - High, Steven C (McGill-Queen's University Press, 2022)
"Point Saint-Charles, a historically white working-class neighbourhood with a strong Irish and French presence, and Little Burgundy, a multiracial neighbourhood that is home to the city's English-speaking Black community, face each other across Montreal's Lachine Canal, once an artery around which work and industry in Montreal were clustered and by which these two communities were formed and divided. Deindustrializing Montreal challenges the deepening divergence of class and race analysis by recognizing the intimate relationship between capitalism, class struggles, and racial inequality. Fundamentally, deindustrialization is a process of physical and social ruination as well as part of a wider political project that leaves working-class communities impoverished and demoralized. The structural violence of capitalism occurs gradually and out of sight, but it doesn't play out the same for everyone. Point Saint-Charles was left to rot until it was revalorized by gentrification, whereas Little Burgundy was torn apart by urban renewal and highway construction. This historical divergence had profound consequences in how urban change has been experienced, understood, and remembered. Drawing extensive interviews, a massive and varied archive of imagery, and original photography by David Lewis into a complex chorus, Steven High brings these communities to life, tracing their history from their earliest years to their decline and their current reality. He extends the analysis of deindustrialization, often focused on single-industry towns, to cities that have seemingly made the post-industrial transition. The urban neighbourhood has never been a settled concept, and its apparent innocence masks considerable contestation, divergence, and change over time. Deindustrializing Montreal thinks critically about locality, revealing how heritage becomes an agent of gentrification, investigating how places like Little Burgundy and the Point acquire race and class identities, and questioning what is preserved and for whom."–
Keywords: Gentrification; Irlandais; Lachine (canal); Noirs; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Travail

Le Québec anglophone: une communauté distincte du reste du Canada? : étude comparative des positions éditoriales de deux journaux anglophones - The Gazette et The Globe and Mail - en rapport avec certains débats publics au Québec et au Canada de 1976 à 1982 - Lacasse, Chantal (Université Laval, 2022)
Keywords: Anglophones; Francophones; Fédéralisme; Indépendantisme; Montreal Gazette; Nationalisme

Les Juifs de la Révolution tranquille: regards d'une minorité religieuse sur le Québec de 1945-1976 - Lacasse, Simon-Pierre (Presses de l'Université d'Ottawa, 2022)
Keywords: Juifs

Negotiating Bella Figura: Inside the Childhood Homes of Six Second-Generation Italian-Canadian Women in Montreal - Massa, Lisa (Université Concordia, 2022)
Keywords: Enfants; Femmes; Italiens

A Fractured Identity: The 1980 Referendum and the Italians of Montreal - Pannunzio, Anthony (Université McGill, 2022)
Keywords: Indépendantisme; Italiens; Nationalisme; Référendums

Remembering the Duvalier era: Resistance, Exile, and Solidarity in the Life Stories of Haitian-Montrealers - Riou, Geneviève (Université Concordia, 2022)
Keywords: Haïtiens

La Maison d’Haïti: Haitian Stories of Resistance and Black Diasporic Activism in Montréal, 1972–1986 - Rochat, Désirée (Histoire sociale / Social History, 2022)
Keywords: Haïtiens; Noirs

Le boulevard Saint-Laurent et son histoire - Tessier, Stéphane (Il était un fois... Montréal Nord, 2022)
issued: 2022-24-00
Keywords: Routes; Saint-Laurent (rue)

Le Montréal juif – (3e partie) - Tessier, Stéphane (Il était une fois...Montréal-Nord, 2022)
Number: 3
Keywords: Juifs

Le Montréal juif – (4e partie et fin) - Tessier, Stéphane (Il était une fois...Montréal-Nord, 2022)
issued: 2022-22-00
Keywords: Juifs

Antijudaïsme et influence nazie au Québec. Le cas du journal L'Action catholique de Québec: 1931-1939 - Anctil, Pierre (Les Presses de l'Université de Montréal, 2021)
"Comment les francophones du Québec ont-ils réagi au début du XXe siècle aux premières manifestations de la diversité culturelle? Ce livre explore l'accueil fait à l'immigration irlandaise, juive est-européenne et chinoise au cours des années 1930 à Québec, tel que vu à travers le prisme du journal L'Action catholique. Il explore en particulier la réaction à l'apparition de commerces juifs dans la capitale provinciale, et en particulier à l'ouverture en 1931 du grand magasin tenu par Maurice Pollack."–
Keywords: Action catholique; Idéologies; Juifs

Redéfinir le Canada et le Québec : les représentations identitaires du Centenaire de la Confédération et de l'Expo 67 chez les journalistes - Blais, Caroline (Université du Québec à Montréal, 2021)
Keywords: Anglophones; Expositions; Francophones; Journalistes

Henri Bourassa, les Franco-Américains et la Première Guerre mondiale - Lamarre, Jean; Dubé, Alexandre (Bulletin d'histoire politique, 2021)
issued: 2021-21-00
Keywords: Américains; Bourassa; Henri; Conscription; Francophones; Guerre

Dal Mediterraneo all’Atlantico: ricordi di migrazione nella Montréal del secondo dopoguerra - Piraro, Sergio (Italian Canadiana, 2021)
Keywords: Italiens

Elites and Scottishness in Montreal: identity, culture and the self in portait photography, 1860-1900 - Regimbald-Roy, Florence (Université McGill, 2021)
Keywords: Notman; William; Photographie; Écossais

By the Rivers of the St Lawrence: The Montreal Jewish Community and Its Postmemory - Robinson, Ira (No better home? Jews, Canada, and the Sense of Belonging, 2021)
Keywords: Juifs

Mainmise sur la contre-culture américaine: la traduction comme véhicule de transfert culturel - Ruschiensky, Carmen (Relire les revues québécoises: histoire, formes et pratiques (XXe-XXIe siècle), 2021)
Keywords: Traduction

Synagogue Architecture in Canada: A Summary History - Stiefel, Barry L. (Journal of the Society for the Study of Architecture in Canada, 2021)
Keywords: Juifs

Idealized Spaces, Internationalized Selves: Japanese Migration to Montreal, Canada, 1990-Present - Tabakow, Elizabeth (Université Concordia, 2021)
Keywords: Japonais

Le Montréal juif – (2e partie) - Tessier, Stéphane (Il était une fois...Montréal-Nord, 2021)
issued: 2021-24-00
Keywords: Juifs

The Rocket, the Riot, and the Revolution: Hockey in French Canada - Valentine, John; Toal, Brandon (Canadian Ethnic Studies / Études ethniques au Canada, 2021)
issued: 2021-23-00
Keywords: Canadien (Club de hockey); Hockey; Nationalisme; Richard; Maurice; Émeutes

Vilna on the St Lawrence: Montreal as the Would-Be Haven for Yiddish Culture - Weiser, Kalman (No better home? Jews, Canada, and the Sense of Belonging, 2021)
Keywords: Juifs

"Un programme unique dans le monde entier": le Congrès juif canadien et la lutte pour le droit à l'égalité "raciale" et religieuse au Québec (1945-1950) - Rainville, Paul-Etienne (Histoire sociale / Social History, 2020)
Number: 120
Keywords: Congrès juif canadien; Juifs

Montréalaises d'origine haïtienne : communauté d'entraide et luttes féministes de 1970 à 1995 - Bélanger, Jasmine (Université du Québec à Montréal, 2020)
Keywords: Femmes; Féminisme; Haïtiens

Frères, repoussoirs ou étrangers? La " diaspora " francophone dans la conscience historique des intellectuels et militants nationalistes du Québec: l’exemple de L’Action nationale (1970-1995) - Bock, Michel (Cahiers Charlevoix, 2020)
Keywords: Action nationale (L'); Francophones; Nationalisme

McGill University’s racial exclusion of Japanese Canadians, 1943-1945 - Elsworthy, Tess (Université McGill, 2020)
Keywords: Japonais; Université McGill

Les " jeunes ", les " amazones ", les " célestes ": les figures de la panique morale sur les drogues à Montréal dans le journal La Patrie, entre 1921 et 1923 - Grenier, Amélie (Bulletin d'histoire politique, 2020)
issued: 2020-22-00
Keywords: Chinois; Criminalité; Femmes; Patrie (La); Réformistes

George M. Brewer et le milieu culturel anglophone montréalais, 1900-1950 - Huston, Lorne; Lefebvre, Marie-Thérèse (Septentrion, 2020)
Keywords: Anglophones; Francophones; Musicien; Musique; Théâtre

GOLDSTEIN, MAXWELL - Lapidus, Steven (Dictionnaire biographique du Canada, 2020)

" Créer ou crever ? ": André Laurendeau et la transmission des particularismes - Lapointe-Gagnon, Valérie (La pensée éducative et les intellectuels au Québec. La génération 1900-1915, 2020)
Keywords: Bilinguisme; Devoir (Le); Journalistes; Langue; Laurendeau; André

Hair 1970. La tribu métissée du Québec - Lavertu, Yves (Éditions Yves Lavertu, 2020)
Keywords: Musique; Noirs; Théâtre

Between Crisis and Preservation: The Canadian Jewish Congress and the Quebec Nationalist Movement, 1976-1980 - Mercado, Ryan (Université Concordia, 2020)
Keywords: Anglophones; Congrès juif canadien; Francophones; Indépendantisme; Juifs; Nationalisme

Civic Identities in Conflict: Montreal's Anglophone and Francophone Private School Girls - Moore, Lisa (Making the Best of It. Women and Girls of Canada and Newfoundland during the Second World War, 2020)
Keywords: Anglophones; Francophones; Étudiants

Black slavery, historians and textbooks: A study of the representation of enslaved people of African descent in Quebec's historiography and history textbooks - Roethlisberger, Susanne (Université McGill, 2020)
Keywords: Africains; Esclaves; Histoire

'' Des Québécois comme les autres ''? Les communautés culturelles dans le projet politique et national du Parti québécois (1968-1981) - Rose, Jérémie (Université de Sherbrooke, 2020)
Keywords: Indépendantisme; Langue; Nationalisme; Partis politique

Divvying up Space: Housing Segregation and National Identity in Early Twentieth-Century Montréal - Sweeny, Robert C. H. (Sharing Spaces: Essays in Honour of Sherry Olson, 2020)
Keywords: Locataires; Logement; Quartiers

Les coopératives de crédit et l'entrée des immigrants juifs dans l'économie montréalaise, 1911-1945 - Taschereau, Sylvie (Le fait urbain, 2020)
Keywords: Juifs

Histoire des communautés noires au Québec et à Montréal (2e partie) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
issued: 2020-22-00
Keywords: Chemins de fer; Musique; Noirs; Travail

Histoire des communautés noires au Québec et à Montréal (3e partie) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
issued: 2020-23-00
Keywords: Haïtiens; Noirs

Le vice et la vertu: le Montréal 1940-1960 - Weintraub, William (Éditions Pierre Tisseyre, 2020)
Translators: _:n57073